WSe2/Al2O3/SnS2SIS Structure Based Self Powered UV-Vis Photodetector - Dwivedi A.K.; Jit S.; Tripathi S. (My University, 2025)
In the current letter, a semiconductor-insulator-semiconductor (SIS) structure based ultraviolet-visible light photodetector is proposed. Tungsten diselenide (WSe2) and tin disulfide (SnS2) are used as semiconductors, and aluminium oxide (Al2O3) is used as an insulator in the proposed photodetector structure. The suggested structure is fabricated on a flexible ITO coated PET substrate using low-cost sol gel spin coating process. At 600 nm wavelength, -1 V bias, and 0.118μ W incident light excitation, the suggested photodetector exhibits responsivity of 225.89 A/W, external quantum efficiency of 4.66× 104 %, detectvity of 1.69× 1012 Jones, and sensitivity of 6.11. The suggested photodetector also exhibits self powered (at 0V bias) response at 600 nm, 650 nm, and 700 nm with sensitivity of 67.24, 81.41, and 57.11 at optical illumination of 0.118μ W. © 1989-2012 IEEE.